NTT: Network Topology Tool for Enhancing NS-2 - AL-Behadili, Hayder Naser Khraibet (Iraqi Journal for Electrical and Electronic Engineering, 2015)
Network Simulator-2(NS-2) is one of the most popular simulation systems that is widely used in the network community. C++ and the object-oriented Tool Command Language (TCL) are both used to write this simulator. C++ works as a background for this simulator, whereas TCL is responsible for scheduling discrete events and network configuration objects. The TCL language is used to write the code of the simulation scenario. NS-2 does not present enough graphical interfaces that could help a researcher reduce the time spent on writing long TCL scripts. Therefore, network researchers spend a great deal of time focusing on how to write the TCL simulation script, which consequently makes the simulation process more difficult. This study presents a novel tool that enhances simulation by using graphical interfaces. The graphical interface is used to create the network topology and convert it into a TCL script. Thus, the process is visualized easily, efficiently, and quickly. This work describes the Network Topology Tool(NTT),which is intended to help researchers who work under the network simulation environment of NS-2. In such a scenario, researchers can create the network topology through an interactive graphical user interface and also they can retrieve and edit it which considered a very important and unique service from the other previous works. This tool will allow professional users to focus on the development of new algorithms or architectures rather than spend time writing scripts for data processing. .